Feedback, gender, and choking under pressure: Evidence from alpine skiing - Christoph Bühren; Martin Gschwend; Alex Krumer (Philipps-University Marburg, School of Business and Economics, 2022)
In alpine skiing competitions, one of the coaches of the participating countries sets the course. This may provide an advantage, but it may also exert higher pressure on the racers. We analyze 40,150 men's and 36,968 women's performances from all competitions in alpine skiing's Slalom, Giant Slalom, and Super Giant disciplines that took place in the World Cups, World Championships, and Olympic Games between the 2001-02 and 2017-2018 seasons. We compare the performance of racers when competing on a course that was set by their compatriot to the performance of the same racers in the same season when the course was set by a coach from another country. Having a compatriot course setter only has an effect in the second (and decisive) run of the most technical discipline Slalom. We find that men fail significantly more often to complete their run when their compatriots set the course, whereas women fail significantly less in the same situation. The most likely drivers of our results relate to gender differences in response to feedback and choking under pressure in skill-based tasks.
Keywords: C33; C93; D91; J16; J24; Z20; 330; Alpine skiing; choking under pressure; gender differences; panel data